Three dimensional flow and mass transfer analysis of a second grade fluid in a porous channel with a lower stretching wall - Khan, Najeeb Alam; Naz, Farah (Zielona Góra: Uniwersytet Zielonogórski)
This investigation analyses a three dimensional flow and mass transfer of a second grade fluid over a porous stretching wall in the presence of suction or injection. The equations governing the flow are attained in terms of partial differential equations. A similarity transformation has been utilized for the transformation of partial differential equations into the ordinary differential equations.
Keywords: second grade fluid; stretching wall; suction; injection